THE EFFECT OF COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. PARTNERS BUILD CEMERLANG TANGERANG CITY - Masripah, Ipah; Amelia, Dahlia; Maharani, Amalia Zahrina (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
The purpose of this study was to analyze the influence of compensation and work discipline on employee performance, compensation on employee performance, work discipline on employee performance at PT Mitra Bangun Cemerlang, Tangerang City. The method used is quantitative, using a Likert scale measuring instrument, with a non- probability sampling technique (sampling is saturated,that is when the number i added, it will not increase the representation so it will not affect the value of the information that has been obtained, as many as 85 employees). The data collection method uses a questionnaire through the Google form. The proposed hypothesis was statistically tested using the SmartPLS 4.0 program. The results showed that compensation had a positive but not significant effect on employee performance because the original sample value was 0.149 and P Values 0.314, work discipline had a positive and significant effect on employee performance because the original sample value was 0.710 and P Values 0.000. Together the compensation and work discipline variables have a moderate effect with an R-Square value of 0.688 or 68.8%.